Implementasi Manajemen Sumber Daya Manusia di Madrasah Aliyah Negeri 2 Kota Malang - Arrifah Putri Nadila; Delvin Pratama (STAI Terpadu Yogyakarta, 2024)
Human Resources (HR) play an important role in improving the quality of education in educational institutions, including Madrasah Aliyah Negeri (MAN). So, good management is needed to achieve madrasah goals. Using a qualitative approach and combined methods, researchers describe the role of HR management, implementation of HR management, and strategies to increase the productivity of teaching and education staff. In achieving maximum results, researchers collected data through observation, interviews and analysis of related documents. The research results show that the role of HR management in MAN 2 Malang City is very important for the institution as seen from the positive impact of its implementation. Apart from that, the implementation of human resource management at MAN 2 Malang City is carried out in the implementation of management functions, namely planning, procurement, coaching and development, promotion and transfer, dismissal, compensation and employee assessment. MAN 2 Malang City also has a strategy to increase the productivity of its human resources, including continuous training and development, providing incentives and rewards, as well as effective coaching and supervision.